Time-domain design for misalignment-tolerant dynamic wireless charging - Quirós, Juan Carlos; Llamas Calvo, Álvaro; Triviño-Cabrera, Alicia; Villagrasa Guerrero, Eliseo (Wiley, 2024)
Wireless power transfer (WPT) offers a safer and more convenient alternative to tradi- tional charging methods. In the automotive sector, dynamic WPT presents a promising solution by reducing battery size and enhancing vehicle usability. The key components of dynamic WPT systems are the coils and their compensation topologies. This paper pro- vides a detailed analysis of these elements to optimize system performance. First, different coil geometries are systematically evaluated using finite element analysis, aiming to iden- tify designs that minimize electrical parameter variations, which can damage electronics and make the control more complex. Then, the most suitable compensation topology is determined through time-domain analysis, which is more accurate under dynamic con- ditions than the commonly used phasor-based approach. This design process based on time-domain analysis is validated with a 100 W dynamic charger prototype, demonstrating the system’s transient behaviour. Experimental results show an efficiency of up to 80% and high tolerance to misalignment under various load conditions.
Keywords: Energía eléctrica - Transporte; Sistemas electroenergéticos; Sistemas de comunicaciones inalámbricos; Wireless power transfer; WPT; coil geometries; misalignment-toleran; dynamic wireless charging